2023
DOI: 10.3390/app13042523
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Gaming in Rehabilitation after Musculoskeletal Injury—User Experience Pilot Study

Abstract: The purposes of this study were twofold: (1) to describe a new technological solution for the rehabilitation of musculoskeletal injuries based on virtual reality (VR) gaming, and (2) to analyze the variation in rated perceived exertion (RPE) and heart rate (HR) of the participants when undergoing a rehabilitation session based on different VR games. Thirty-seven participants aged 23.7 ± 7.0 years tested during five customized VR games to provide a complete rehabilitation session after a musculoskeletal injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…Irini Patsaki [16] applied VR rehabilitation training in the treatment of COPD patients to effectively increase the treatment effect. In rehabilitation training after musculoskeletal injuries [17], scholars have developed virtual reality-based rehabilitation training to help athletes recover from musculoskeletal injuries. In low vision rehabilitation [18], researchers summarized the application of virtual reality technology in visual field expansion and visual acuity improvement in the rehabilitation of low vision people, and found that virtual reality equipment can expand the visual field and improve visual acuity.…”
Section: Related Work 21 Application Of Virtual Reality Technology In...mentioning
confidence: 99%
“…Irini Patsaki [16] applied VR rehabilitation training in the treatment of COPD patients to effectively increase the treatment effect. In rehabilitation training after musculoskeletal injuries [17], scholars have developed virtual reality-based rehabilitation training to help athletes recover from musculoskeletal injuries. In low vision rehabilitation [18], researchers summarized the application of virtual reality technology in visual field expansion and visual acuity improvement in the rehabilitation of low vision people, and found that virtual reality equipment can expand the visual field and improve visual acuity.…”
Section: Related Work 21 Application Of Virtual Reality Technology In...mentioning
confidence: 99%